2022
DOI: 10.36416/1806-3756/e20210393
|View full text |Cite
|
Sign up to set email alerts
|

Use of remdesivir in patients with COVID-19: a systematic review and meta-analysis

Abstract: Objective: Studies in the literature regarding the use of remdesivir to treat COVID-19 patients have shown conflicting results. This study sought to answer questions related to the use of remdesivir for the treatment of patients hospitalized with moderate to severe COVID-19. Methods: This was a systematic review and meta-analysis including phase 3 randomized clinical trials (RCTs) and observational cohort studies selected from various databases, comparing patients hospitalized with moderate to severe COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
3
7
0
4
Order By: Relevance
“…In our study, remdesivir was associated with an increased length of hospital stay but decreased odds of mechanical ventilation. Although some studies and meta-analyses suggested that remdesivir did not reduce all-cause mortality and the need for invasive mechanical ventilation [ 13 - 15 ], others, similar to our findings, showed that remdesivir was associated with a significantly reduced need for invasive mechanical ventilation or extracorporeal membrane oxygenation in COVID-19 patients [ 16 - 18 ]. Many studies agree that the use of remdesivir was associated with improved time to recovery and recovery rate, especially in non-mechanically ventilated patients [ 19 - 21 ].…”
Section: Discussionsupporting
confidence: 72%
“…In our study, remdesivir was associated with an increased length of hospital stay but decreased odds of mechanical ventilation. Although some studies and meta-analyses suggested that remdesivir did not reduce all-cause mortality and the need for invasive mechanical ventilation [ 13 - 15 ], others, similar to our findings, showed that remdesivir was associated with a significantly reduced need for invasive mechanical ventilation or extracorporeal membrane oxygenation in COVID-19 patients [ 16 - 18 ]. Many studies agree that the use of remdesivir was associated with improved time to recovery and recovery rate, especially in non-mechanically ventilated patients [ 19 - 21 ].…”
Section: Discussionsupporting
confidence: 72%
“…Remdesivir is a nucleoside analog prodrug, which is metabolized intracellularly to an adenosine triphosphate (ATP) analog that inhibits the activity of the viral RNA polymerase (sold under the brand name Veklury, Gilead) [ 187 ]. Its function as a broad-spectrum viral RNA-dependent RNA polymerase (RdRp) inhibitor is well studied and it is effective against several positive and negative-sense RNA viruses including Ebola, hepatitis C virus, respiratory syncytial virus, as well as SARS-CoV-2 in vitro and in vivo [ 188 , 189 ]. In contrast, it only shows low antiviral activity against the segmented negative-sense RNA viruses IAV, Lassa Virus, and Crimean-Congo hemorrhagic fever virus, which is likely facilitated by differences in the structural architecture of the polymerase active sites which disfavors remdesivir as a substrate for RNA synthesis [ 190 , 191 , 192 ].…”
Section: Antiviral and Immunomodulatory Treatments For Covid-19mentioning
confidence: 99%
“…Поскольку ингибирование фер-мента препятствует репликации вируса в инфицированных клетках, он проявляет антивирусную активность против ряда одноцепочечных РНК-содержащих вирусов, включая коронавирусы MERS и SARS [6,7]. Официальное разрешение для использования ремдесивира при лечении COVID-19 было выдано FDA (Управление по санитарному надзору за качеством пищевых продуктов и медикаментов США) 1 мая 2020 г. Недавний метаанализ показал, что использование ремдесивира способствовало увеличению частоты выздоровления на 6% (95% ДИ: 3-9, р = 0,004) и клинического улучшения на 7% (95% ДИ: 1-14, р = 0,02), однако не оказывало статистически значимого влияния на показатели смертности [8]. Эти результаты были подтверждены другим независимым метаанализом, не выявившим значения ремдесивира в рамках снижения летальности у госпитализированных пациентов с COVID-19 [9].…”
Section: Introductionunclassified